Biological activities and variation of symbiotic fungi isolated from Coral reefs collected from Red Sea in Egypt - Abd El-Rahman, Tahany M.A. (Mycology, 2020)
Ten specimens of coral reefs were collected from the Red Sea in the Ein El-Sukhna region. Fungal isolation was done using two media, Dextrose Yeast Extract Agar (DYA) and Rose Bengal Agar (RBA). The morphological traits identified 18 fungal isolates belonging to the phyla Ascomycota, Mucoromycota and Deuteromycota. Five genera in three orders have been isolated: Eutrotiales (Aspergillus, Penicillium and Byssochlamys), Mucorales (Rhizopus) and Moniliales (Curvularia). The heat mapping clustering of the isolated fungi declared that Aspergillus and Penicillium were the most frequently isolate fungi in coral reefs. It was found that A. fumigatus colonised eight coral samples with 80% colonisation rate. Moreover, about 50% of the isolated fungal species were specific to one coral reef only such as A.candidus and A.carneus isolated from Isophyllastrea rigida only, A.japonicus and A.ochraceopetaliformis from Glaxaea fascicularis, A.niger van Tieghem from Porites astreoides, A.sydowii, A.terreus and P.waksmanii from Cladocora arbuscula, P.janthinellum from Pterogorgia guadalupensis and Curvularia tuberculata, Byssochlamys spectabilis and Rhizopus oryzae from Acropora humilis. Biological activities (antimicrobial, antioxidant antiradical and cytotoxicity) of the most predominant fungal species were investigated. The antimicrobial activity of coral fungal filtrates were investigated against six pathogenic bacteria including Escherichia coli ATCC11775, Neisseria gonorrhoeae ATCC19424, Pseudomonas aeruginosa ATCC10145, Streptococcus faecalis ATCC19433, Staphylococcus aureus subsp. aureus ATCC25923, Bacillus subtilis subsp. spizizenii ATCC6633 and two pathogenic yeast including Candida albicans ATCC7102 and Candida parapsilosis ATCC22019. Most of these fungal filtrates exhibited moderate to high antibacterial activities against both gram positive and gram negative bacteria, however it showed relatively low bioactivity towards the pathogenic Candida species. Investigating the free radical scavenging activity using DPPH reagent showed low to moderate bioactivities. The highest cytotoxic activity against liver cancer cell line Hep-G2 with an IC(50) values of 18.8 µg/ml was exhibited by Aspergillus ochraceopetaliformis MN083316 and a metabolomics study was done on the ethyl acetate extract of this strain using LC-ESI-MS fingerprints leading to the isolation and purification of compound 1. Using 1D and 2D NMR techniques compound 1 was identified as ditryptophenaline. Compound 1 exhibited a strong antimicrobial, antioxidant activities as well as cytotoxic activities against MCF-7 and HEPG2 with IC(50) values of 5.8 and 7.6 mmole, respectively. The objective of this study, isolation of Coral-reef associated fungi and studying their biological activities to produce the most active secondary metabolite which might possess a novel biological activity.